Pemberian Grasi Oleh Presiden Terhadap Terpidana Tindak Pidana Pembunuhan Ditinjau Dari Perpektif Keadilan, Kepastian, Dan Kemanfaatan Hukum - Cristina Natalia Sinaga; Arman Tjoneng (Jurnal Hukum Lex Generalis, 2024)
This study aims to illustrate that pardon should be given to individuals who truly admit their guilt and serve to complete justice, but not to erase the convict's guilt. Antasari Azhar, through his attorney, twice submitted a request for pardon to the president. The first request for pardon was rejected, but the second request was granted by the President. In the second granting of pardon, Based on the Supreme Court's decision in letter number 21/Panmud Pid/IX/2016/18/MA/2016 dated September 30, 2016, the President issued Presidential Decree 1/G/2017 on January 16, 2017. From the principles of justice and legal benefits, the granting of pardon to Antasari Azhar is considered to deviate from the two legal principles, because in accordance with Article 2 paragraph (3) of Law Number 5 of 2010 concerning amendments to Law Number 22 of 2002, a request for pardon can only be submitted once. From the perspective of the principle of legal certainty, the granting of pardon by the President to Antasari Azhar through Presidential Decree 1/G/2017, based on the submission of a pardon request twice, clearly contradicts Article 2 paragraph (3) which states that a pardon can only be submitted once.